Pengaruh Kepuasan Kerja Dan Kompensasi Terhadap Kinerja Karyawan Qini Mart Pagendingan - Lesmana, Pahmi; Sutrisna, Arga; Risana, Dudu (Jurnal Pakar Manajemen, 2024)
This research was conducted to determine and analyze the influence of Job Satisfaction and Compensation on the Performance of Qini Mart Pagendingan Employees. The method used is a quantitative method using a descriptive approach and conducting a survey method. The number of samples used was 45 employees of Qini Mart Pagendingan. The data used is primary data. The analytical tool used is multiple regression using SPSS 25. The results of the research show that Job Satisfaction has a Very Good classification, Compensation has a Very Good classification, while employee performance has a Very Good classification for Qini Mart Pagendingan Employees. Simultaneously, Job Satisfaction and Compensation have a significant influence on Employee Performance at Qini Mart Pagendingan. Partially, employee job satisfaction has a significant influence on the performance of Qini Mart Pagendingan employees. Partially, compensation has a significant influence on the performance of Qini Mart Pagendingan employees.